PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, BELANJA MODAL DAN PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI KABUPATEN KUANTAN SINGINGI - Asnita Asnita; Harlen Harlen; Ando Fahda Aulia (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of gross regional domestic product (GRDP), capital expenditures and human development on poverty in Kuantan Singingi Regency. Methods of data analysis using analytical methods using multiple linear regression analysis. The results of this study indicate that gross regional domestic product (GRDP) has a significant negative and significant effect on poverty in Kuantan Singingi Regency, meaning that poverty reduction is due to an increase in gross regional domestic product (GRDP) will increase the ability to meet needs so that they can get out of poverty. line of poverty. Capital expenditure has a positive and significant effect on poverty in Kuantan Singingi Regency, meaning that an increase in capital expenditure actually encourages higher poverty. This is contrary to the hypothesis which states that capital expenditure has a negative and significant effect on poverty in Kuantan Singingi Regency. The human development index (HDI) has a positive and significant effect on poverty in Kuantan Singingi Regency, which means that partially changes in the human development index (IPM) are able to positively and significantly affect changes in poverty.